1985
DOI: 10.1039/c39850001370
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of 1,2,3-triazines with Grignard reagents

Abstract: Monocyclic 1,2,3-triazines reacted with Grignard reagents to form adducts due to N-2 and C-5 attack together with p-su bstituted acrylaldehydes and N-substituted pyrazoles; the results show that the N-2, C-4, and C-5 positions are reactive towards Grignard reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 1 publication
0
51
0
Order By: Relevance
“…The C4 addition of methoxide has been reported, addition of Grignard reagents at C4 (PhMgBr) or C5 (MeMgI) has been disclosed, and the reaction of a lithium reagent (PhLi) at C4 has been described. 16 C4 and C6 disubstitution (methyl) on 1,2,3-triazine has been reported to redirect the addition of a nucleophile to C5 and, remarkably, N2 as well. 16 Like the work detailed herein, C4 addition in these studies has been reported to proceed with in situ loss of nitrogen (N 2 ) and hydrolysis of the resulting imine, providing the corresponding α,β-unsaturated aldehyde.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The C4 addition of methoxide has been reported, addition of Grignard reagents at C4 (PhMgBr) or C5 (MeMgI) has been disclosed, and the reaction of a lithium reagent (PhLi) at C4 has been described. 16 C4 and C6 disubstitution (methyl) on 1,2,3-triazine has been reported to redirect the addition of a nucleophile to C5 and, remarkably, N2 as well. 16 Like the work detailed herein, C4 addition in these studies has been reported to proceed with in situ loss of nitrogen (N 2 ) and hydrolysis of the resulting imine, providing the corresponding α,β-unsaturated aldehyde.…”
mentioning
confidence: 99%
“…This site (C4) also constitutes the most electron-deficient center of the reacting molecular orbital (LUMO) of 1 but it is not the center that bears the largest LUMO molecular orbital coefficient. 16 …”
mentioning
confidence: 99%
“…1 H and 13 C NMR spectra were recorded on Bruker 500 spectrometer ( 1 H at 500 MHz and 13 C at 125 MHz) and Agilent 400MR DD2 spectrometer…”
Section: Scheme 4 Synthetic Applications and Control Experimentsmentioning
confidence: 99%
“…For example, the parent triazine slowly decomposes in methanol at room temperature, which suggests that nucleophilic attack of methanol occurs in the solution. Also, softer nucleophiles undergo a redox reaction with triazine (1) to give 2,5-dihydro derivatives 73 without ring substitution [112] (Scheme 20.16).…”
Section: 243mentioning
confidence: 99%